The Protection of Celebrity Name in China: After the ‘乔丹’ Case by the SPC of China - Zhang, Huaiyin (Indonesian Journal of International Law, 2021)
The Supreme People’s Court (SPC) case of ‘乔丹’, brought by Michael Jordan against Qiaodan Sports, is a landmark case over the protection of the right to the personal name in the People’s Republic of China (PRC). In the retrial proceeding, the SPC gave eight exhaustive explanations to the disputed questions and eventually reversed the lower court’s decision. After studying the judgment, this article finds that a famous foreign name can be protected by Chinese Trademark law only when it satisfies three conditions: First, the specified name enjoys a certain popularity in China and is well-known to the concerned public; second, the concerned public uses the specified name to refer to the original person of that name; and third, there has already been a stable match between the specific name and the original person of that name. Although China mainly adopts the “right to name” for the legal protection of celebrity names, the right to name is a kind of personal right, difficult to protect economic benefits derived from celebrities’ names fully. Comparing Germany’s extended protection model of personality rights and the United States model of “right of publicity,” this article suggested that China tries to introduce the United States model to protect the celebrity name’s right.